Correction in the article by Abdelrazek Ali et al. “Management of collaterals after Glenn procedure and its impact on patients with a single ventricle: a single-center study”, REC Interv Cardiol. 2024;6:296-304 - Yasmin Abdelrazek Ali; Nehad El-Sayed Nour El-Deen; Ghada Samir Elshahed (REC: Interventional Cardiology (English Ed.))
.alineup td, .alineup th { vertical-align: top; text-align: left; } .txtsang{ padding: 0 40px; } In the article by Abdelrazek Ali et al. “Management of collaterals after Glenn procedure and its impact on patients with a single ventricle: a single-center study” (REC Interv Cardiol. 2024;6:296-304), Table 3 has been modified for clarification. Denominators have been added to explain the percentages. The amended version of Table 3 is: Table 3. Angiographic assessment of collaterals Catheterization N = 56 Aortopulmonary collaterals ...